2004
DOI: 10.1530/rep.1.00214
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis as a potential mechanism for microbial defense of mouse placental trophoblast cells

Abstract: Trophoblast giant cells are active phagocytes during implantation and post-implantation. Phagocytosis decreases during placental maturation as the phagocytic function of nutrition is gradually replaced by the direct uptake of nutrients by the labyrinth zone trophoblast. We hypothesize that, after placental maturation, trophoblast cells maintain phagocytic functions for purposes other than nutrition. This study employs histological techniques to examine the ability of trophoblast cells to phagocytose microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
4
36
0
5
Order By: Relevance
“…A number of recent studies examined the mice trophoblast phagocytosis in vivo and in vitro leading to similar results (Schlesinger and Koren, 1967;Delgado and Santos-Buch, 1978;Pavia, 1983;Drake and Rodger, 1987;Albieri et al, 2001;Amarante-Paffaro et al, 2004;Neres et al, 2008). Fetal transmission of Trypanosoma cruzi experimentally infected in pregnant females depended on pathogenicity of the strain and trophoblast phagocytosis.…”
Section: Phagocytosis As a Defense Mechanism At The Maternal Fetal Inmentioning
confidence: 76%
See 2 more Smart Citations
“…A number of recent studies examined the mice trophoblast phagocytosis in vivo and in vitro leading to similar results (Schlesinger and Koren, 1967;Delgado and Santos-Buch, 1978;Pavia, 1983;Drake and Rodger, 1987;Albieri et al, 2001;Amarante-Paffaro et al, 2004;Neres et al, 2008). Fetal transmission of Trypanosoma cruzi experimentally infected in pregnant females depended on pathogenicity of the strain and trophoblast phagocytosis.…”
Section: Phagocytosis As a Defense Mechanism At The Maternal Fetal Inmentioning
confidence: 76%
“…In addition, phagocytosis of zymosan particles administered in pregnant female on day 13.5 of gestation can be seen at placental trophoblast giant cells for subsequent 12 hours. In culture, the internalization of these particles was relevantly accelerated and intensified after trophoblast activation by IFN-γ (Albieri et al, 2001;Amarante-Paffaro et al, 2004). Furthermore, comparatively to zymosan, Escherichia coli particles were internalized by placental trophoblast more rapidly, suggesting that phagocytosis may depend on the nature of the target organism and possibly to specific patterns of recognition (Amarante-Paffaro et al, 2004).…”
Section: Phagocytosis As a Defense Mechanism At The Maternal Fetal Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of prior immunity, these proinflammatory mediators function as the first line of defense against parasites and are crucial for controlling infection; otherwise, parasites grow rapidly and overwhelm the host, causing severe illness and fatality. The inflammatory mediators exert toxic effects on parasites by initiating a variety of effector mechanisms, such as cytotoxicity by free radicals, phagocytosis, complement activation, and cell and antibody-mediated adaptive immune responses (5,9,(11)(12)(13). For example, IFN-␥ is a potent immunostimulatory cytokine that primes macrophages for the efficient production of cyto-kines, including TNF-␣, IL-12, IL-6, and reactive oxygen and nitrogen free radicals.…”
mentioning
confidence: 99%
“…It has been shown that C3b bound to membrane cofactor protein (MCP), or C3-like factor bound to complement receptors CR1 and CR3 is involved in the fertilization of humans and frogs (Anderson et al, 1993;Cervoni et al, 1992;Llanos et al, 2000). Phagocytic activity in mouse placental trophoblasts is enhanced by C3b probably through CR1 (Albieri et al, 1999;Amarante-Paffaro et al, 2004). Furthermore, embryotrophic function of iC3b, the cleaved product of C3b, in mouse blastocysts probably through the rodent complement receptor-related protein y (Crry) and CR3 has been reported (Lee et al, 2004).…”
Section: Binding Of C3 To Rat Embryosmentioning
confidence: 99%